Inclusive engineering in the restaurant industry - Kuzmin, Oleg; Chemakina, Oktyabrina; Kuzmin, Anton; Kuzmin, Dmytro (My University, 2024)
Інклюзивний інжиніринг у закладах ресторанного господарства спрямований на створення безбар’єрного середовища, забезпечення доступності та оптимізацію енергоефективності для комфорту всіх відвідувачів, включаючи осіб із особливими потребами

Inclusive engineering in the restaurant industry focuses on creating barrier-free environments, ensuring accessibility, and optimizing energy efficiency to provide comfort for all individuals, including those with special needs
Keywords: кафедра технології ресторанної і аюрведичної продукції; інклюзивний інжиніринг; мікрокліматичні умови; енергоефективність; ресторанне господарство; inclusive engineering; microclimatic conditions; energy efficiency; restaurant industry